Potencial antimicrobiano de extratos de uma população de Byrsonima coccolobifolia Kunth (Mirixi-caju) de Boa Vista, Roraima - Silva, Semiramys Moreira (2009)
Byrsonima coccolobifolia Kunth popularly known as “mirixi-caju” belongs to the Genus Byrsonima and Family Malpighiaceae. It is one of the most abundant species of tropical savanna regions of Brazilian tropics which has been used by traditional medicine in the form of infusion of the leaves and bark to treat wounds as antiseptic agents. In this study we evaluated the antimicrobial activity of methanol extract, chloroform, ethyl acetate and ethanol, produced from the aerial parts and stem bark of individuals of B. coccolobifolia, against bacterial species (Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Serratia marcescens) and fungal (Candida albicans). The tests for antimicrobial activity were performed following the method of Kirby and Bauer and minimum inhibitory concentration of active extracts. The results indicated that the extracts tested showed activity against strains of Gram (+), especially S. aureus, with the largest halos presented by extracts of ethyl acetate, chloroform and methanol obtained from the stem bark. When tested against C. albicans showed partially active, with no difference between the plant parts used or the solvent employed to prepare the extract. Thus, the use of B. coccolobifolia can infer an effective alternative especially against bacterial infections caused by S. aureus.